Assessing ventilation rate measurements in a mechanically ventilated laying hen facility. (24th November 2018) - Rosa, E; Arriaga, H; Calvet, S; Merino, P
ABSTRACT: Gaseous emission in laying hen facilities affects animal production performance and the environment. Emission is ruled by gas concentration and ventilation rate (VR), which are the key parameters to estimate precise emission factors. In this work, VR were assessed in a mechanical ventilated laying hen facility under Mediterranean climate conditions. The study was performed during a complete production cycle from July 2015 to October 2016. Direct hot wire anemometer (HWA) and fan rotational speed methods, and indirect CO2 mass balance method were used to assess the VR. Mean VR was 5.3 ± 2.9 m 3 h −1 hen −1 for the HWA method. The mean uncertainty of VR based on the HWA method was 8.5%, and it varied among ventilation stages from 2.3 to 12.8%. Uncertainty was higher in warm season (9.6%) than in cold season (5.4%). In relation to fan rotational speed method, mean VR was 5.9 ± 3.3 m 3 h −1 hen −1, which accounts for 8.3% more than the HWA method. According to the results, the fan rotational speed method would be less sensitive than the HWA method for assessing VR. VR was 6.3 ± 2.1 m 3 h −1 hen −1 for the CO2 balance method, which estimated lower VR values in warm season compared to the laser tachometer (LT) method (–5%) but higher values compared to the HWA method (+5%). In contrast, it estimated higher values in cold season compared to the HWA method (+23%) and LT method (+17%). Correlation analysis showed a strong correlation between the CO2 balance method and both direct methods (R = 0.85 and 0.86 for HWA and LT, respectively).